2022
DOI: 10.3389/fonc.2022.997306
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating non-lactating mastitis and malignant breast tumors by deep-learning based AI automatic classification system: A preliminary study

Abstract: Objective: To explore the application values of deep-learning based artificial intelligence (AI) automatic classification system, on the differential diagnosis of non-lactating mastitis (NLM) and malignant breast tumors, via its comparation with traditional ultrasound interpretations and the following interpretation conclusions made by the sonographers with various seniorities.Methods: A total of 707 patients suffering from breast lesions (475 malignant breast tumors and 232 NLM), were selected from the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Both GLM and BC typically present as breast masses with indistinct borders and rm consistency, and may be accompanied by enlarged ipsilateral axillary lymph nodes. Although modern research has improved the non-invasive differential diagnosis of GLM and BC through various radiological techniques, such as sonogram radiomics model 22 , contrast-enhanced ultrasound 23 , ultrasound elastography 24 , deep-learning based AI automatic classi cation system 25 , and ARFI elastography 26 , the gold standard for diagnosing GLM still requires tissue biopsy. In some cases, multiple biopsies may be necessary for clinical differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both GLM and BC typically present as breast masses with indistinct borders and rm consistency, and may be accompanied by enlarged ipsilateral axillary lymph nodes. Although modern research has improved the non-invasive differential diagnosis of GLM and BC through various radiological techniques, such as sonogram radiomics model 22 , contrast-enhanced ultrasound 23 , ultrasound elastography 24 , deep-learning based AI automatic classi cation system 25 , and ARFI elastography 26 , the gold standard for diagnosing GLM still requires tissue biopsy. In some cases, multiple biopsies may be necessary for clinical differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature has highlighted the efficacy of deep learning in assessing breast images, helping detect malignant and benign breast tumors for both lactating and non-lactating women [49 -54]. This has helped improve the precision of breast ultrasound and mammogram examinations, involving the use of medical imaging previously taken in medical facilities to enhance the evaluation of breast-related illnesses and allow better accuracy in diagnosis for medical personnel [53]. Nevertheless, these studies relied on images gathered from specialized equipment found only in healthcare facilities, not extending their evaluation on external body images, making their main focus on helping healthcare practitioners in diagnosis.…”
Section: Current Research Supporting Lactating Mothersmentioning
confidence: 99%
“…These applications include cancer screening and diagnosis [ 37 , 38 , 39 , 40 ], diagnosis and classification [ 41 , 42 , 43 , 44 ], predicting prognosis and treatment response [ 45 , 46 , 47 , 48 , 49 ], automated segmentation [ 50 , 51 , 52 , 53 , 54 ], and radiology-pathology correlation (radiogenomics) [ 55 , 56 , 57 , 58 ]. In particular, within the field of diagnosis and classification, the ability of AI models to classify benign vs. malignant tumours has been shown to achieve high accuracy, sensitivity, and specificity in various organs, such as in the case of breast [ 59 , 60 , 61 ], prostate [ 62 , 63 ], lung [ 38 , 64 , 65 , 66 ], and brain lesions [ 67 , 68 ]. This review article aims to provide an overview of the current evidence on the effectiveness of machine learning in differentiating bone lesions on various imaging modalities.…”
Section: Introductionmentioning
confidence: 99%